CRABP1 protects the heart from isoproterenol-induced acute and chronic remodeling. Issue 3 (March 2018) - Park, Sung Wook; Persaud, Shawna D; Ogokeh, Stanislas; Meyers, Tatyana A; Townsend, DeWayne; Wei, Li-Na
Abstract : Excessive and/or persistent activation of calcium-calmodulin protein kinase II (CaMKII) is detrimental in acute and chronic cardiac injury. However, intrinsic regulators of CaMKII activity are poorly understood. We find that cellular retinoic acid-binding protein 1 (CRABP1) directly interacts with CaMKII and uncover a functional role for CRABP1 in regulating CaMKII activation. We generated Crabp1 -null mice (CKO) in C57BL/6J background for pathophysiological studies. CKO mice develop hypertrophy as adults, exhibiting significant left ventricular dilation with reduced ejection fraction at the baseline cardiac function. Interestingly, CKO mice have elevated basal CaMKII phosphorylation at T287, and phosphorylation on its substrate phospholamban (PLN) at T17. Acute isoproterenol (ISO) challenge (80 mg/kg two doses in 1 day) causes more severe apoptosis and necrosis in CKO hearts, and treatment with a CaMKII inhibitor KN-93 protects CKO mice from this injury. Chronic (30 mg/kg/day) ISO challenge also significantly increases hypertrophy and fibrosis in CKO mice as compared to WT. In wild-type mice, CRABP1 expression is increased in early stages of ISO challenge and eventually reduces to the basal level. Mechanistically, CRABP1 directly inhibits CaMKII by competing with calmodulin (CaM) for CaMKII interaction. This study demonstrates increased susceptibility of CKO mice to ISO-induced acute and chronic cardiac injury due to, at least in part, elevated CaMKII activity. Deleting Crabp1 results in reduced baseline cardiac function and aggravated damage challenged with acute and persistent β-adrenergic stimulation. This is the first report of a physiological role of CRABP1 as an endogenous regulator of CaMKII, which protects the heart from ISO-induced damage.